PENGARUH TAKARAN PUPUK ORGANIK PLUS BATUBARA DAN PEMBERIAN BERBAGAI DOSIS PUPUK KIMIA TERHADAP PRODUKSI TANAMAN JAGUNG MANIS DI LAHAN PASANG SURUT - Wuriesyliane, Wuriesyliane; Syafrullah, Syafrullah; Hawayanti, Erni; Iskandar, Joni (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2021)
This research was conducted to find out and get a dose of organic fertilizer plus coal and dose of chemical fertilizers influential best to the growth and production of sweet corn (Zea Mays saccharata Sturt.). this research was conducted in one of the land owned farmers in the village srimenanti kecamatan Tanjung Lago kabupaten banyuasin Sumatra the South. From May to July 2019. The research method used in this study was Factorial Randomized Block Design with 9 combinations of 3 treatment replications and 4 sample plants. The treatment referred to is as follows: a. Organic Fertilizer Plus P1 = 250 kg / ha (4.375 g / plant), P2 = 500 kg / ha (87.5 g / plant), P3 = 750 kg / ha (13.125 g / plant). b. Compound NPK Chemical Fertilizer K1 = 100 kg / ha (1.75 g / plant), K2 = 150 kg / ha (2.625 g / plant), K3 = 200 kg / ha (3.5 g / plant). Organic fertilizer treatment plus dosage of 750 kg / ha (13.125 g / plant). The combination treatment of organic fertilizer plus coal compound chemical fertilizer with a dose of 750 kg / ha (13.125 g / plant) dose of 150 kg / ha (2.625 g / plant) gave the highest yield on the weight of cobs of sweet corn.